2021
DOI: 10.1090/conm/775/15591
|View full text |Cite
|
Sign up to set email alerts
|

A survey on the blow-up method for fast-slow systems

Abstract: In this document we review a geometric technique, called the blow-up method, as it has been used to analyze and understand the dynamics of fast-slow systems around non-hyperbolic points. The blow-up method, having its origins in algebraic geometry, was introduced to the study of fast-slow systems in the seminal work by Dumortier and Roussarie in 1996, whose aim was to give a geometric approach and interpretation of canards in the van der Pol oscillator. Following Dumortier and Roussarie, many efforts have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 123 publications
0
4
0
Order By: Relevance
“…are satisfied. The first condition in (25) implies that the map is locally orientation-preserving and that S is normally hyperbolic and attracting near (x, y). The second guarantees that there are no fixed points in the reduced map.…”
Section: Formal Embeddings In the Normally Hyperbolic Regimementioning
confidence: 99%
See 1 more Smart Citation
“…are satisfied. The first condition in (25) implies that the map is locally orientation-preserving and that S is normally hyperbolic and attracting near (x, y). The second guarantees that there are no fixed points in the reduced map.…”
Section: Formal Embeddings In the Normally Hyperbolic Regimementioning
confidence: 99%
“…Thus, alternative methods are needed. A number of works have shown that an adaptation of the well-known geometric blow-up method [10,25,30,32] can be applied to study of discretized fast-slow ODEs with singularities in (i) [1,14,46,44]. The approach adopted in these works relies in an important way on scaling properties of the discretization parameter, but there are significant obstacles to the extension of this approach to the study of general fast-slow maps, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The equation (32) implies that μ = μ(εt) depends only on the slow time and acts as a parameter in (31). For μ > 1 − I 0 , equation ( 31) has the oscillating solution φ = ϕ μ(t) given by (13). Note that the parameters of this solution can depend on the slow time.…”
Section: Appendix A: Multiscale Averaging In the Regime Of Fast Oscil...mentioning
confidence: 99%
“…Investigating the dynamics of such multiscale systems has lead to the development of a number of useful asymptotic and geometric methods, see Refs. [9][10][11][12][13] to name just a few.…”
Section: Introductionmentioning
confidence: 99%